Empowering Digital Pioneers: Optimalisasi Strategi Pemasaran di Era Transformasi Digital - Firmansyah, Muhammad Azwar; Walda, Akbel Varianto Walda; Rahmadi, Deddy (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Abstract This study aims to empower local communities in rural areas through digital marketing training tailored for small business actors and community leaders. Implemented in Karangnongko Village, the program adopted a participatory and practice-based training model. The materials covered content creation, branding, and social media marketing strategies using platforms like TikTok, Instagram, and WhatsApp Business. The results showed improved digital literacy, increased participant awareness of online marketing strategies, and the establishment of practical skills to independently promote local products and tourism. This initiative demonstrates the potential of localized digital training as a model for inclusive digital transformation. Abstrak Penelitian ini bertujuan memberdayakan masyarakat pedesaan melalui pelatihan digital marketing yang ditujukan kepada pelaku UMKM dan tokoh masyarakat. Program dilaksanakan di Desa Karangnongko dengan pendekatan partisipatif dan berbasis praktik. Materi mencakup pembuatan konten, branding, dan strategi pemasaran melalui media sosial seperti TikTok, Instagram, dan WhatsApp Business. Hasil menunjukkan peningkatan literasi digital peserta, kesadaran terhadap strategi pemasaran daring, serta keterampilan praktis dalam mempromosikan produk dan wisata lokal secara mandiri. Inisiatif ini membuktikan efektivitas pelatihan digital berbasis komunitas dalam mendukung transformasi digital yang inklusif.